Assessment of Novel Semen Evaluation Technologies and Breed Comparisons in Yearling Beef Bulls - A. R. Hartman; I. E. Batey; D. M. Grieger; K. E. Fike (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:The objectives were 1) to evaluate the iSperm, when conducting breeding soundness exams (BSE) on bulls by comparing sperm motility to a technician’s assessment and 2) to evaluate correlations between sperm response to reactive oxygen species (ROS) and functional sperm measurements. Study Description:Ejaculates were collected via electroejaculation from yearling bulls as part of a BSE. All BSE were conducted by one veterinarian and ejaculates were evaluated by a single technician. Additional sperm motility analysis was conducted with the iSperm analyzer. Ejaculates meeting minimum thresholds for passing a BSE were diluted and sent overnight for flow cytometry evaluation. Data were analyzed using Pearson’s correlation coefficients in SAS. Results:Both gross and progressive motilities were significantly (r= 0.30; 0.38;P<0.001) correlated to the technician’s assessment of progressive motility. Percentage of live spermatozoa with positive ROS status was correlated (r= 0.53;P<0.001) with percentage progressive motility. Percentage of live spermatozoa with negative ROS status was moderately correlated with percentage spermatozoa exhibiting secondary abnormalities (r= 0.33;P= 0.02). Percentage live spermatozoa that had disrupted acrosomes was strongly correlated with percentage live spermatozoa with negative ROS (r= 0.66;P<0.001) and moderately negatively correlated with percentage live spermatozoa with positive ROS (r= -0.31;P= 0.04). Percentage of live spermatozoa with positive ROS status was correlated (r= 0.58;P<0.001) with percentage of spermatozoa with active mitochondrial membranes. Percentage of live spermatozoa with positive ROS status was strongly correlated (r= 0.92;P<0.001) with percentage of live spermatozoa with intact acrosomes. The Bottom Line:The iSperm can be used to produce semen assessments similar to those of a trained technician and may offer a useful tool for producers to perform on-farm semen analysis. Sperm health and function continue to be related to negative ROS status.
Keywords: sperm motility; morphology; concentration